Perancangan Sistem Peminjaman Barang Inventaris di Dinas Komunikasi dan Informatika Kabupaten Situbondo - Fiki Hasan; A. Homaidi; Iqbal Hamdani WM (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
The management of inventory at the Department of Communication and Informatics of Situbondo Regency is still carried out manually, which often leads to various problems such as recording errors, loss of important information, and difficulties in monitoring the status of borrowed or available items. This condition results in suboptimal utilization of inventory, decreased work efficiency, and disruption of overall public service performance. To address these issues, this study designs and implements an integrated web-based inventory loan information system. The system development adopts the System Development Life Cycle (SDLC) method with the Waterfall model, consisting of requirements analysis, design, implementation, testing, and continuous maintenance. Research data were collected through direct field observations, interviews with related staff, and literature review of relevant references. The developed information system is designed to facilitate the entire process of borrowing, including loan requests, approval by officers, transaction recording, item returns, and automated report generation. With the implementation of this web-based system, all processes can be centrally managed, thereby improving the speed and accuracy of data recording, simplifying monitoring of item status, and significantly reducing the risk of information loss. In addition, the system is expected to enhance transparency, accuracy, and accountability in inventory management while providing tangible positive contributions to improving performance and service quality within the Department of Communication and Informatics of Situbondo Regency.